Farmers’ willingness to accept compensation for ginkgo conservation: evidence from rural Taixing, China - Dai, Xiaoqing; Pu, Lijie; Jiang, Debang; Zhang, Ying; Rao, Fangping (Frontiers in Sustainable Food Systems, 2024)
Numerous potential socioeconomic benefits provided by ginkgo resources have been identified but these have been threatened due to insufficient conservation over recent decades. Economic compensation is essential to induce enthusiasm for conservation. This paper examines the farmers’ willingness to accept ginkgo conservation compensation as well as other influencing factors based on survey data from 208 households. The results show that: first, the compensation amounts for the three different ginkgo conservation values are 820.86, 249.03, and 71.29 yuan per tree, respectively. Second, the overall compensation value is 388.17 yuan per tree with an average of 8430.83 yuan per household. Third, factors that influence the conservation compensation values are size-specific. Specifically, for large ginkgoes, a given respondent’s age, gender, job, household income, the number of large ginkgoes and arable land area are the most important factors. For medium ginkgoes, the area of arable land and farmers’ willingness to protect ginkgo trees are the key determining factors. By contrast, the requisite factors are different for small size ginkgo trees. A given respondent’s job, the arable land area and farmers’ perception of the importance of conducting conservation for local development are found to have significant impacts. These findings provide a useful base for assessing the conservation value for this endangered and valuable forest resource. Furthermore, the results also indicate that a size-based payment for farmers’ ginkgo conservation behaviors can be a useful economic tool to induce and deepen the latter’s conservation efforts.